Checking semantics in UML models: use cases diagrams - Gómez, Rodolfo (2002)
Constraints add to the semantics to UML models in the form of statements which are expected to hold for the model to be considered correct, i.e., to satisfy system requirements. Constraints are considered in the UML metamodel as adornments attached to model elements, and languages like OCL allow for different statements to be expressed. Despite several CASE-like tools are currently supporting UML diagram and constraint definition, as far as we know none of them provides support for verification and maintainance of constraint consistency. Having this kind of facility helps users in the design of UML models, specially when these models are complex and the impact of model evolution is difficult to trace. This work studies how constraint consistency may be compromised when model elements are introduced or modified during system development. Focus is over use case diagrams, which suffice to highlight a number of important issues related with consistency maintenance. We introduce procedures for verifying and maintaining constraint consistency, and illustrate them using a simple constraint specification language. Our goal is to make a first step in the development of tools for automatic verification and mantainance of model semantics.